The U-Pb detrital zircon signature of West Antarctic ice stream tills in the Ross embayment, with implications for Last Glacial Maximum ice flow reconstructions. Issue 6 (13th November 2014) - Licht, Kathy J.; Hennessy, Andrea J.; Welke, Bethany M.
Abstract: Glacial till samples collected from beneath the Bindschadler and Kamb ice streams have a distinct U-Pb detrital zircon signature that allows them to be identified in Ross Sea tills. These two sites contain a population of Cretaceous grains 100–110 Ma that have not been found in East Antarctic tills. Additionally, Bindschadler and Kamb ice streams have an abundance of Ordovician grains (450–475 Ma) and a cluster of ages 330–370 Ma, which are much less common in the remainder of the sample set. These tracers of a West Antarctic provenance are also found east of 180° longitude in eastern Ross Sea tills deposited during the last glacial maximum (LGM). Whillans Ice Stream (WIS), considered part of the West Antarctic Ice Sheet but partially originating in East Antarctica, lacks these distinctive signatures. Its U-Pb zircon age population is dominated by grains 500–550 Ma indicating derivation from Granite Harbour Intrusive rocks common along the Transantarctic Mountains, making it indistinguishable from East Antarctic tills. The U-Pb zircon age distribution found in WIS till is most similar to tills from the west-central Ross Sea. These data provide new specific targets for ice sheet models and can be applied to pre-LGM deposits in the Ross Sea.